Stuxnet revisited: From cyber warfare to secret statecraft. - Lindsay, Jon R. (Journal of Strategic Studies, 2025)
The Stuxnet attack on Iran's nuclear program is an outlier in the history of cyber conflict. While espionage and subversion are prevalent, serious cyber-physical damage remains rare. Stuxnet has thus had an outsized influence on debates about cyber warfare, for visionaries and skeptics alike. This seminal case deserves a second look in light of more recent evidence and the evolving literature on cybersecurity. Rather than a precious incident of cyber warfare, Stuxnet can be better understood as a tool of covert diplomacy. Indeed, Stuxnet illustrates key features of secret statecraft such as indefinite duration, institutional subversion, clandestine organization, and escalation management.